2007
DOI: 10.1002/cpa.20225
|View full text |Cite
|
Sign up to set email alerts
|

Infinite time aggregation for the critical Patlak‐Keller‐Segel model in ℝ2

Abstract: We analyze the two-dimensional parabolic-elliptic Patlak-Keller-Segel model in the whole Euclidean space R 2 . Under the hypotheses of integrable initial data with finite second moment and entropy, we first show local in time existence for any mass of "free-energy solutions", namely weak solutions with some free energy estimates. We also prove that the solution exists as long as the entropy is controlled from above. The main result of the paper is to show the global existence of free-energy solutions with init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
266
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 260 publications
(276 citation statements)
references
References 45 publications
5
266
1
4
Order By: Relevance
“…(1.2) This model shares some features with the classical Patlak-Keller-Segel model for chemotaxis [33,46] without diffusion, see [16,12,13,26] for the state of the art in this problem. Here, the main similarity is the possible formation of a finite time point concentration and the main difference the strong singularity of the potential in the Patlak-Keller-Segel system.…”
Section: Introductionmentioning
confidence: 92%
“…(1.2) This model shares some features with the classical Patlak-Keller-Segel model for chemotaxis [33,46] without diffusion, see [16,12,13,26] for the state of the art in this problem. Here, the main similarity is the possible formation of a finite time point concentration and the main difference the strong singularity of the potential in the Patlak-Keller-Segel system.…”
Section: Introductionmentioning
confidence: 92%
“…In fact, the classical Patlak-Keller-Segel [35,24] system, see [12,10,11], corresponds to the choice of the Newtonian potential in R 2 as interaction, W = 1 2π log |x| with linear diffusion. In the case without diffusion, a notion of weak measure solutions was introduced in [36] for which the author proved global-in-time existence, although uniqueness is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to more careful studies, more refined conditions on initial data yielding blowup have been identified (see [2]) and the detailed quantitative way of the occurrence of blowup has been shown, see for instance [11,16,17]. Next the situation when the initial data have critical mass has been studied ( [4][5][6]). Finally, in the case of a quasilinear system, for any space dimension n critical nonlinearities have been identified such that if φ and ψ satisfy the subcritical relation, then solutions to (1.1) stay bounded for any time, while for those satisfying the supercritical relation solutions blow up in finite time independently of the magnitude of initial mass provided the data are concentrated enough, see [10].…”
Section: (· T) V(· T) = −D U(· T) V(· T)mentioning
confidence: 99%